Balancing Sexual Autonomy, Responsibility, and the Right to Privacy: Principles for Criminalizing Sex by Deception. Issue 5 (August 2021) - Scheidegger, Nora
Abstract: Due to the reconceptualization of rape and other sexual offenses as violations of one's sexual autonomy, consent has replaced the element of force as the focal point of rape law. This shift to a "consent model" of rape has prompted much discussion about the scope of sexual autonomy and the problem of "rape by deception" in legal scholarship. Most theorists of consent argue that certain forms of deception invalidate any token of consent in the same way as forcible sexual contact. However, there is also a widely shared concern that criminalizing sex-by-deception poses serious problems in terms of drawing the line between deceptions that violate sexual autonomy and deceptions that do not. This Article offers an account of principles that should be considered when examining legal cases related to sex-by-deception. These principles are examined and articulated in a way that strikes a balance between responsibility, autonomy, and rights such as the right to privacy.